2018
DOI: 10.1016/j.foodchem.2018.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Exploring reserve lots of Cymbopogon citratus , Aloysia citrodora and Thymus × citriodorus as improved sources of phenolic compounds

Abstract: Given the increasing consumers demand for novelty, tea companies have been presenting new added value products such as reserve lots of aromatic plants. Herein, infusions from different lots of three aromatic plants were assessed in terms of phenolic composition (HPLC-DAD-ESI/MS) and antioxidant properties (reducing power, free radical scavenging and lipid peroxidation inhibition capacity). Cymbopogon citratus (C. citratus; main compound 5-O-caffeoylquinic acid) and Aloysia citrodora (A. citrodora; prevalence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Based on the obtained results, we can consider that OpTC extract exerts a strong in vitro antioxidant potential, acting especially as a free-radical scavenger (best results obtained for DPPH assay – 79.28 ± 0.41 mg TE/g). Moreover, results obtained in TBARS assay confirm the ability of OpTC extract to inhibit lipid peroxidation, its activity being comparable or stronger than other Thymus extracts ( T. × citriodorus, T. algeriensis ), including the common thyme ( T. vulgaris ) [51] , [52] , [53] . Similarly, the effectiveness of OpTC as oxidative haemolysis inhibitor was highlighted, the obtained results confirming an inhibitory capacity higher than the positive control (Δ t Trolox at 60 min being 21.80 ± 0.25 and Δ t Trolox at 120 min being 43.50 ± 0.82).…”
Section: Resultsmentioning
confidence: 74%
“…Based on the obtained results, we can consider that OpTC extract exerts a strong in vitro antioxidant potential, acting especially as a free-radical scavenger (best results obtained for DPPH assay – 79.28 ± 0.41 mg TE/g). Moreover, results obtained in TBARS assay confirm the ability of OpTC extract to inhibit lipid peroxidation, its activity being comparable or stronger than other Thymus extracts ( T. × citriodorus, T. algeriensis ), including the common thyme ( T. vulgaris ) [51] , [52] , [53] . Similarly, the effectiveness of OpTC as oxidative haemolysis inhibitor was highlighted, the obtained results confirming an inhibitory capacity higher than the positive control (Δ t Trolox at 60 min being 21.80 ± 0.25 and Δ t Trolox at 120 min being 43.50 ± 0.82).…”
Section: Resultsmentioning
confidence: 74%
“…(T. citriodorus) or lemonscented thyme is considered to be a hybrid between T. pulegioides and T. vulgaris (Lundgren & Stenhagen, 1982). T. citriodorus is native from Southern Europe, cultivated in the Mediterranean area and, due to its lemon flavour, is mainly used for culinary purposes, either as seasoning or as herbal tea (Rita, Pereira, Barros, & Ferreira, 2018). Several bioactivities have been attributed to this species, namely anti-oxidant and cytoprotective effects as well as anti-bacterial and anti-radical scavenging activity (Sacchetti et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…These bioactivities might be intrinsically correlated with its chemical composition, although data to support this are still scarce. The reported chemical composition of non-volatile extracts of T. citriodorus includes rosmarinic acid, as the major compound, cinnamic acid derivatives, such as caffeic acid, and derivatives of luteolin, eriodictyol, quercetin, chrysoeriol, and apigenin (Pereira, Peres, Silva, Domingues, & Cardoso, 2013;Rita et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…The previous study reported the RP test of thyme spices: Rita et al, 2018, assessed the infusion extract (polar solvent), of Thymus × citriodorus (and other spices), they found a concentration of 228 ± 0.003 µg/ml 43 . This value is higher than that of hydrométhanolic and ethyl acetate (87.81 ± 3.23 and 108.08 ± 6.44 respectively), thus is lower activity than of this study.…”
Section: Antioxidant Activitiesmentioning
confidence: 99%